System Dynamics Model of COVID-19 Pandemic Situation: The Case of Phuket Thailand - Pornphol, Putsadee; Chittayasothorn, Suphamit (My University, 2020)
The outbreak of COVID-19 disease worldwide impacts the world health, social, and economic situations enormously. At present, there is no vaccines for the virus nor medicine which could cure them. Cities locked down and physical distancing seem to be good options to help reduce infection and casualties from the disease. However, these options may not convince members of the public since their daily life and economy are affected. Business cannot be carried on as usual and people suffer. Lockdowns and social distancing are often resisted. This research project uses the System Dynamics Simulations Model to simulate the infection of and recovery from the COVID-19 disease of populations within an administration area. The Susceptible, Infectious, Recovered (SIR) model is employed in the System Dynamic modelling. The case study area is Phuket, Thailand, which is a popular tourist destination. The contact rates among infected people and other people in Phuket are found to be relatively higher than other cities which are not tourist destinations.
Keywords: Causal Loop Diagram; Contact Rates; COVID-19; Phuket; SIR Model; System Dynamics